Improving and expanding hedgerows—Recommendations for a semi‐natural habitat in agricultural landscapes. Issue 1 (19th February 2023) - Staley, Joanna T.; Wolton, Robert; Norton, Lisa R.
Abstract: Hedgerows provide habitat, shelter and resources for many species including functionally important taxa and threatened species. Hedgerows store carbon both above‐ and below‐ground and provide a range of other ecosystem services. Policies incentivizing increases in the extent and quality of hedgerows require evidence to determine how these increases may best support a wide range of taxa and to improve hedgerow habitat quality. Here, available evidence for increasing hedgerow extent and improving their quality is discussed in the context of current conservation policy. Moderate evidence supports a substantial increase in average hedgerow extent from 4.2 km/km 2 to around 10 km/km 2 in the United Kingdom, to optimize support for many wildlife taxa, habitat connectivity and carbon storage. Evidence also supports the development of wider and structurally denser hedges with more diverse structures and management approaches, and hedgerow networks that are well connected with each other and with other semi‐natural habitats. However, barriers may hinder the implementation of hedgerow policies, and there remain substantive gaps in the evidence base. Knowledge gaps include the current quality or condition of UK hedges, understanding in which landscape contexts new hedges would best be planted to support biodiversity, the role of hedgerows in connectivity as species' ranges change under a future climate, and whether an increase in hedgerow extent might increase the spread of invasive species, tree pests or diseases. These gaps must be filled if conservation policies, including future agri‐environment schemes, are to ensure that hedgerows reach their considerable potential in aiding nature's recovery and addressing climate change. Abstract : Improving and expanding hedgerows—evidence shows that more, better quality hedges are needed in UK agricultural landscapes to support thriving wildlife. Current government and NGO conservation policies advocate an increase in hedgerow extent. We discuss knowledge gaps and barriers that may hinder the implementation of these policies.